Oil Revenue Shocks and the Current Account Balance Dynamics in Nigeria: New evidence from Asymmetry and Structural Breaks - Fasanya, Ismail O.; Adetokunbo, Abiodun; Ajayi , Felix O. (SPOUDAI Journal of Economics and Business, 2018)
In this paper, we model the relationship between oil revenue and current account balance dynamics in Nigeria using quarterly data from 1987Q1 to 2015Q4. We employ both the Linear ARDL and Nonlinear ARDL models and we also account for multiple structural breaks using a test that allows for multiple structural changes in regression models. The following were noticed from our analyses. First, we observe the existence of an asymmetric effect on the current account balance both in the short and long run. Second, accounting for structural breaks play an important role when modelling the relationship between oil revenue and current account balance. Third, the paper finds that oil revenue has a significant positive effect on current account balance, however, puzzling that both positive and negative shocks affect the current account balance in the same manner. Overall, the positive changes in oil revenue have considerably larger impact than negative changes. The implications for policy are designed based on gathered findings. JEL Classifications: C51, F32, Q43